Infrastructure needed to facilitate quality online higher education - Segovia-García, Nuria (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
Virtual higher education is growing significantly and is characterised by the need to effectively articulate technology and the academic and instructional process. This study has sought to analyse the requirements for institutions to offer a quality service close to the needs of students. To this end, a survey was administered to a random sample of 350 students. The results would confirm the strong association between factors related to technological infrastructure, academic service, and institutional support. These results can be a reference to be considered by HEIs when planning their virtual programmes.